Tantangan Implementasi Manajemen Berbasis Sekolah Pada Sd Berrapor Merah - Sri Handayani; Faisal Ahmad Purwantob; Salma Raya Fitri Rivana Dellany; Indana Zulfa Wahyu; Isnaeni Nur Ladzunie; Maria Melani Ika Susanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study discusses the implementation of School-Based Management (SBM) in SD Negeri 1 Jatipuro. This school is included in the category of schools with a red report card, which means it has many problems in the quality of education. The main problems faced are the low quality of education, lack of community participation, limited resources such as facilities and infrastructure, and lack of enthusiasm for learning from students. The purpose of this study is to determine whether the implementation of SBM can be a solution to overcome these problems and improve the quality of education in schools. The study was conducted using a case study approach and literature study. Data were collected through direct observation of the school, interviews with the principal, distributing questionnaires to educators and parents, and studying relevant books and articles. After the data was collected, the researcher analyzed it using a descriptive-qualitative method, namely describing the results based on facts in the field. The results of the study showed that the implementation of MBS had begun at the school. Some positive things that have been running are openness in budget management, and the involvement of the school committee in making important decisions. However, the implementation has not been completely smooth because there are still obstacles, such as lack of supporting facilities, low parental involvement, and some educators who are not ready to accept change. Although not perfect, the implementation of MBS is considered a fairly good initial step to improve the school management system and the quality of student learning in schools that are experiencing many challenges.